Framing exposure to excessive and improper lighting as light-public health - Mirko Ancillotti; Elisa Conticelli; Simona Tondelli; Deborah Mascalzoni (Discover Public Health)
Abstract Excessive or improper lighting can affect human health and well-being. However, lighting is seldom considered within frameworks analyzing the interrelations between the urban environment and the health and well-being of communities. Lighting-related concerns are often conceptualized and discussed in environmental terms through the light pollution frame. Positively, this frame emphasizes human responsibility for the environmental detriment and animal harm caused by lighting and promotes the discussion of aesthetics and existential dimensions connected to nocturnal darkness. Negatively, it is flawed with epistemological shortcomings and normativity; it is prone to the risk of ideological and political polarisation and tends to underemphasize the health implications of excessive and improper lighting. This study addresses this gap by arguing for the advantages of a public health framing of lighting-related concerns. In particular, it highlights how this perspective can better capture the health implications of lighting and inform urban policies. Placing light concerns within a public health framework entails presenting a relatively known landscape that resonates with the value systems of virtually everyone. This approach supports the creation of a common, multi-stakeholder space in discussions on lighting policies, balancing considerations of urban security, safety, inclusivity, and accessibility as different dimensions of diverse populations’ health and well-being. By emphasizing the public health dimension, this study contributes to the discourse on lighting as a determinant of health and well-being. Such a holistic framework aligns with the United Nations Sustainable Development Goal 3 on good health and well-being by fostering conditions that advance health for all, addressing lighting not merely as an environmental issue but as a critical public health priority.